Prevalence, associated factors, and association of intimate partner violence and suicidal behaviors among women of reproductive age in Asia: Protocol for a systematic review and meta-analysis of cross-sectional studies - Mantaka Rahman; Habiba Kabir; Anika Naowar Chowdhury; Md. Babu Raihan Mia; Tamal Saha; Afroza Tamanna Shimu; Ummul Khair Alam (PLoS ONE, 2026)
Intimate partner violence (IPV) is strongly linked to suicidal behaviors (ideation, plans, attempts), affecting 1 in 3 women globally, with prevalence varying across regions. Sociocultural and economic factors shape IPV and SB risk differently. This review will estimate prevalence, risk factors, and associations of IPV and SBs among women of reproductive age in Asia to provide region-specific evidence for targeted interventions. We will systematically search PubMed, Scopus, PsycINFO, Web of Science, EMBASE, CINAHL, and Google Scholar for studies published up to 30 November 2025, following PRISMA guidelines. The search will also include grey literature and citation chaining, using keyword truncation, string searches, and standardized indexing terms. Cross-sectional observational studies among Asian women (19–45 years) exposed to intimate partner violence (physical, psychological, sexual) will be included, reporting suicidal behaviors (ideation, plans, attempts) compared with unexposed women. Only English-language, peer-reviewed studies will be considered, while reviews, abstracts, and unpublished studies will be excluded. Two independent reviewers will screen studies for the central concepts of “Intimate Partner Violence (IPV)” and “Suicidal Behaviors (SB)”, with disagreements resolved by a third reviewer. Data on prevalence, associated factors, mediator variables, and numerical estimates of IPV–SB associations will be extracted. Meta-analysis using a random-effects model will be conducted alongside a narrative synthesis. Findings will be visualized with forest and funnel plots, heterogeneity assessed using the Q Cochrane statistic and I² index, and subgroup and sensitivity analyses performed. Risk of bias will be evaluated using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. Early identification of psychological distress using culturally validated tools, combined with understanding context-specific drivers of IPV, is essential for preventing suicidal behaviors among Asian women of reproductive age. Findings from this review will inform targeted interventions, guide policy, and address gender norms that perpetuate violence and elevate mental health risks.